1996
DOI: 10.1021/jp953027r
|View full text |Cite
|
Sign up to set email alerts
|

Chain Mechanism of Radical-Initiated Ligand Exchange in PtCl42- in Aqueous Solution

Abstract: The reactions of organic radicals, which are generated by pulse radiolysis in aqueous K 2 PtCl 4 solutions containing an alcohol or ether, are traced by optical absorption and conductivity methods. Upon attack by 1-hydroxyalkyl or 1-alkoxyalkyl radicals, PtCl 4 2-disappears in a chain reaction, in which Cl -ligands are substituted by H 2 O. 2-Hydroxyalkyl radicals do not initiate the chain. The final product of attack by 1-hydroxyalkyl radicals is colloidal platinum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…It thus seems that an autocatalytic mechanism contributes to colloid formation, possibly via a catalyzed reduction of Au−III by the formaldehyde formed in eq 2. An autocatalytic mechanism in the radiolytic reduction of PtCl 4 2- has previously been found …”
Section: Discussionmentioning
confidence: 93%
“…It thus seems that an autocatalytic mechanism contributes to colloid formation, possibly via a catalyzed reduction of Au−III by the formaldehyde formed in eq 2. An autocatalytic mechanism in the radiolytic reduction of PtCl 4 2- has previously been found …”
Section: Discussionmentioning
confidence: 93%
“…Earlier, Creighton and Eadon calculated the optical absorption of platinum nanoparticles based on the Mie theory and demonstrated that a plasmon peak should appear at 215 nm . Experimentally, Henglein et al showed that a peak actually exists around 215 nm for nanoparticles prepared by the radiolytic reduction of PtCl 4 2– . , Nevertheless, until recently most of platinum particles that have been prepared were smaller than ∼10 nm and showed negligible absorption in the visible region. However, it was recently reported that Pt particles greater than 100 nm could be prepared under laboratory conditions .…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows the absorption spectra of an aqueous solution containing a 3:1 molar ratio of Pt/Pd (metal ions) along with PEG (stabilizer) and 2-propanol, as a function of the sonication time. Together with a strong absorption below 300 nm, the initial spectrum shows absorption bands centered at~325 and 390 nm likely arising from PtCl 4 2− and Pd(CH 3 COO) 2 species, respectively [39,40]. Within 1 h of sonication, the above-mentioned absorption bands disappeared, and a clear dark brown solution was obtained.…”
Section: Resultsmentioning
confidence: 98%